Sustainability assessment and rating of buildings : developing the methodology SBToolPTeH - Mateus, Ricardo (2011)
Although sustainable building is a multidimensional concept, attention to the issue often focuses solely on environmental indicators, ignoring the substantial importance of social, economic and cultural indicators. Building sustainability involves various relations between built, natural and social systems and therefore comprises a complex of different priorities that require consideration at each stage of a building’s life-cycle. To cope with this complexity and to support sustainability systematic, holistic and practical approaches to building design need to be developed. The main objective of a systematic methodology is to support the development of a building design that achieves the most appropriate balance between the different sustainability dimensions, and is, at the same time, practical, transparent and flexible enough to be easily adapted to different types of buildings and technology. It is the aim of this paper to present an innovative approach for developing building sustainability assessment and rating, and to contribute to the evolution of generic methodology and international understanding by introducing an approach which takes the different dimensions of sustainability into account. The scope of the methodology presented in this paper (SBToolPTeH) is to assess the sustainability of existing, new and renovated residential buildings in urban areas, specifically in the Portuguese context.